Trade with Nominal Rigidities: Understanding the Unemployment and Welfare Effects of the China Shock - Andrés Rodríguez-Clare; Mauricio Ulate; Jose P. Vasquez (Center for Economic Studies and ifo Institute (CESifo), 2022)
We present a dynamic quantitative trade and migration model that incorporates downward nominal wage rigidities and show how this framework can generate changes in unemployment and labor participation that match those uncovered by the empirical literature studying the "China shock." We find that the China shock leads to average welfare increases in most U.S. states, including many that experience unemployment during the transition. However, nominal rigidities reduce the overall U.S. gains by around one fourth. In addition, there are seven states that experience welfare losses in the presence of downward nominal wage rigidity that would have experienced gains without it.
Keywords: F10; J20; 330; trade; unemployment; China shock; downward nominal wage rigidity